Formulasi Dan Uji Stabilitas Sabun Padat Transparan Ekstrak Biji Pala (Myristica fragrans Houtt) - Fauziah Fauziah; Nurmalia Zakaria; Azmalina Adriani; Nazirah Nazirah; Khamdiyah Indah Kurniasih (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Transparent solid soap is a solid texture soap. Solid soap formulated with the addition of nutmeg extract serves as a drug agent to treat infections of the skin that cause bacteria. This study aims to determine the formulation and stability of the solid soap from the nutmeg seed extract. The research method is an experimental method. The treatments used were concentrated in formula 1 (0.5%), formula 2 (1%) and formula 3 (1.5%). The research parameters were organoleptic test, pH test, foam stability test, moisture content test. The results showed that the form of transparent solid soap from nutmeg seed extract was very dense, varied in color, namely clear chocolate (Formula 1), brown (Formula 2) and dark chocolate (Formula 3) with a less nutmeg odor. This soap has a pH of 11 and has different levels of foam. Formula 1 with initial foam height of 6.7 cm and final foam height of 5.5 cm (moisture content 5.17%). Formula 2 has a foam height of 7.4 cm and a final foam height of 5.8 cm (water content 4.99%), while formula 3 has a foam height of 8 cm and a final foam height of 6.3 cm (moisture content is 4.96%). The conclusion is the transparent solid soap made from nutmeg extract has met the soap requirements as stipulated by the Indonesian National Standard for the soap stability test (SNI 3532-2016).